Pengaruh Efektivitas Komite Audit, Efektivitas Internal Audit dan Kualitas Audit terhadap Pengungkapan Sukarela - Purnomo, Hanny; Bernawati, Yustrida (E-Jurnal Akuntansi, 2020)
The purpose of this study is to prove the truth, internal audit, internal audit, and audit quality on voluntary disclosures in companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sample was selected using a purposive sampling technique to obtain a sample of 100 companies, the hypothesis was taken using multiple linear regression. The results of this study prove the importance of audit audits, internal audits, and audit quality applied to company voluntary disclosures. Keywords: Effectiveness of Audit Committee; Internal Audit; Audit Quality; Voluntary Disclosure.